2020
DOI: 10.1186/s12954-020-00424-w
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among people who use drugs in Iran: a systematic review, meta-analysis, and trend analysis

Abstract: Background People who use drugs (PWUD) are considered as one of the main at-risk populations for Hepatitis B virus (HBV) infection. We conducted a systematic review on the prevalence of HBV infection among PWUD in Iran. Methods Consistent with PRISMA guideline, international (Medline, Web of Science, Scopus, and Embase) and national (Scientific Information Database) databases were searched using a comprehensive search strategy up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…The highest prevalence of HBsAg (60.8%) and HBcAb (85.1%) in Iran was observed in Afghan refugees in a camp in the south of Iran [33]. On the other hand, a meta-analysis has shown that the prevalence of HBsAg among non-injecting people who use drugs and PWID in Iran is 2.9% and 4.8%, respectively [34]. The present study showed that the prevalence of HBsAg in incarcerated individuals with a history of drug injection was 3.01%.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of HBsAg (60.8%) and HBcAb (85.1%) in Iran was observed in Afghan refugees in a camp in the south of Iran [33]. On the other hand, a meta-analysis has shown that the prevalence of HBsAg among non-injecting people who use drugs and PWID in Iran is 2.9% and 4.8%, respectively [34]. The present study showed that the prevalence of HBsAg in incarcerated individuals with a history of drug injection was 3.01%.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to another study, there has been no significant trend of hepatitis B virus (HBV) infection among this group in 1990–2017 timespan in the country [50]. On the other hand, there has been a significant decline in the prevalence of both HIV and hepatitis B virus infection among PWID in a similar period in Iran [6,50]. The latter decline has been mostly attributed to the extensive harm reduction measures initiated in 2002 and expanded since 2005, including needle syringe and opioid substitution treatment programs [51,52].…”
Section: Discussionmentioning
confidence: 96%
“…However, we found no significant difference between the HIV prevalence among non‐injecting PWUD before 2007 and afterward. Similarly, according to another study, there has been no significant trend of hepatitis B virus (HBV) infection among this group in 1990–2017 timespan in the country [50]. On the other hand, there has been a significant decline in the prevalence of both HIV and hepatitis B virus infection among PWID in a similar period in Iran [6,50].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A meta-analysis study in 2017 estimated that the prevalence rates of HBsAg and anti-HBcAb in Iran’s general population were 1.79% (1.67% to 2.32%) and 13.59% (12.92% to14.29%), respectively [ 2 ]. Moreover, the pooled pre-valence of HBsAg among people who use drugs through injecting and otherwise was 4.8% and 2.9%, respectively [ 3 ]. Additionally, the pooled prevalence of HBsAg among Iranian hemodialysis patients was 4% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%